North American Critical Theory After Postmodernism
X, 249 p.
Keywords: In a series of interviews this book explores the formative experiences of a generation of critical theorists whose work originated in the midst of what has been called 'the postmodern turn,' including discussions of their views on the evolution of critical theory over the past 30 years and their assessment of contemporary politics.